Relative macrofaunal biomass reduced under an enriched salmon farm, Pelorus Sound, Aotearoa-New Zealand. (August 2020) - Handley, Sean J.; Morrisey, Don; Depree, Craig; Carter, Megan; Mejía Torres, Luis A.
Abstract: We compared changes in the benthos associated with discharges from a salmon farm at a low-flow location in Pelorus Sound, Aotearoa-New Zealand to the Pearson and Rosenberg model (PRM). As predicted by PRM, benthic enrichment resulted in significant increases in abundance of small, opportunistic macrofauna beneath salmon farm cages. In contrast, at reference sites we found fewer but larger, rare species. When estimates for biomass were calculated from macrofaunal size-classes, reference sites averaged 4.86 times more biomass and 4.35 times greater diversity than farm sites – results also consistent with the PRM. Farm sites favoured deposit feeders at the expense of suspension feeders and grazers. We discuss the significance of large rare species that contributed most to reference biomass estimates that appear under threat from multiple anthropogenic stressors. Highlights: Small, opportunistic macrofauna dominated beneath salmon farm sites. Large rare species contributed more to biomass estimates at reference sites. The farm favoured deposit feeders at the expense of suspension feeders and grazers.